2016
DOI: 10.17554/j.issn.2224-3992.2016.05.665
|View full text |Cite
|
Sign up to set email alerts
|

Possible Prophylaxes of Aloe Vera Gel Ingestion to Butyrate Metabolism

Abstract: There is a growing interest in butyrate because its impact on epigenetic mechanisms will lead to more specific and efficacious therapeutic strategies for the presentation and treatment of different disease ranging from genetic/metabolic conditions to neurological degeneration disorders. The dietary natural source of butyrate through a high fiber diet or butyrate produced by fermentation of non-digestive fiber, such as acemannan in Aloe Vera leaf gel, is a highly appealing approach to present a simple and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In an early our in vitro study, the fermentation production of butyric acid was confirmed by endophytic bacteria within Aloe vera gel [15] and possible prophylaxes of Aloe vera gel ingestion to butyrate metabolism was suggested [16] . Present investigation shows the identification of Bacillus cereus, B.licheniformis, Lactobacillus paralimentarium and Clavispora lusitaniae by use of MALDI-TOF/MS, a rapid, reliable and costdeacetylases (HDACs).…”
Section: Introductionmentioning
confidence: 88%
“…In an early our in vitro study, the fermentation production of butyric acid was confirmed by endophytic bacteria within Aloe vera gel [15] and possible prophylaxes of Aloe vera gel ingestion to butyrate metabolism was suggested [16] . Present investigation shows the identification of Bacillus cereus, B.licheniformis, Lactobacillus paralimentarium and Clavispora lusitaniae by use of MALDI-TOF/MS, a rapid, reliable and costdeacetylases (HDACs).…”
Section: Introductionmentioning
confidence: 88%
“…Possible efficacy of longterm ingestion of Aloe vera gel metabolites on insulin sensitivity has been proposed by Yagi A [1] , and the brain-liver-intestine circuit was considered for coordination between insulin sensitivity and glucose production. On exploration of health maintenance with Aloe vera gel long-term ingestion, Yagi A group [2] proposed that the dietary natural source of butyrate produced by fermentation of acemannan in Aloe vera gel, is a highly appealing approach to present a simple and relatively low risk method to potentially improve outcomes in aged people with brain troubles. Krautkramer KA group [3] demonstrated that gut microbiota alter host histone acetylation and methylation in the multiple host tissues; the proximal colon, the liver and fat tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary natural source of butyrate through a high fiber diet or butyrate produced by fermentation of non-digestive fiber, such as acemannan in Aloe vera gel, is highly appealing approach to present a simple and selectively lower risk method to potentiate the improved outcomes in aged people with brain dysfunctions. Recently, Yagi et al [21] discussed the potential pharmacological effect of butyrate as a histone deacetylase inhibitor on insulin resistance and energy expenditure, and as prodrugs for ulcerative colitis and cancer, and the gut-liver axis in preclinical treatment.…”
mentioning
confidence: 99%